Clopidogrel effectiveness in patients with ST elevation myocardial infarction - O. V. Sirotkina; E. V. Bogdanova; N. A. Bogan’kova; A. N. Stolyarova; T. V. Mvilova; S. A. Boldueva (Кардиоваскулярная терапия и профилактика)
Aim. То analyse the effectiveness of clopidogrel therapy (Zilt®) in patients with myocardial infarction (MI), according to genetic variants of Р-450 ЗА cytochromes, platelet adenosine diphosphate (ADPH) receptors, fibrinogen and collagen.Material and methods. The study included 34 patients with ST elevation MI (MI-ST). Antiaggregant therapy effectiveness was assessed based on ADPH-induced platelet aggregation (photometric method by Bom). Polymorphisms A-293G CYP3A4, G6986A CYP3A5, C18T and G36T P2Y12, Leu33Pro GPIIIa, C-154T and T13254C GPVI, C807T GPIa were detected by polymerase chain reaction method, with subsequent restriction endonuclease-based analysis.Results. Clopidogrel therapy was associated with reduced aggregation — 23,5±2,5 %., 32,9±2,8 %, 40,0±3,1% and 16,3±2,6 Щ, 27,0±3,0 %, 35,0±3,4 % at points 1 and 2 for 2,5, 5 and 10 mkM of ADPH, respectively (p<0,04, p<0,l). Individuals with polymorphisms G36T P2Y12, C-154T and T13254C GPVI, C807T GPIa, as well as people with no protective allele T18 P2Y12, demonstrated higher aggregation at baseline and more effective reduction associated with therapy. One exception, Leu33Pro GPIIIa mutation, was observed, linked to no reduction in platelet aggregation. Clopidogrel was more effective in participants with A-293G CYP3A4 mutation, while no clear associations were observed for G6986A CYP3A5.Conclusion. Clopidogrel effectively reduced platelet aggregation in patients with MI-ST, with one exception — Leu33Pro GPIIIa mutation.